The Effect of Promotion Strategy and Social Media on the Attractiveness of Prospective New Students Moderated by Brand Image on Study Program Selection at the University of 17 August 1945 Jakarta - Fina Yuliana; Endyastuti Pravitasari (Fakultas Ekonomi Universitas Kadiri, 2023)
This article aims to test and analyze the effect of Promotion Strategy and Social Media on the Attractiveness of prospective new students moderated by Brand Image on the selection of study programs at the University of 17 August 1945 Jakarta. The population in this study used a sample of 232 respondents, who were final year students from SMA, SMK, MA, and Paket C. The data collection technique used simple random sampling by distributing research questionnaires in the form of Google Forms through social media and socialization at school. The data processing method in this study uses Smart PLS software which is used to test the hypothesis. The results of this study indicate that promotional strategies and social media and brand image are proven to have a positive and significant effect on attractiveness. Brand image has a significant effect and can moderate the effect of promotional strategies on attractiveness, and brand image is proven to be significant and can moderate the effect of social media on attractiveness. The results of this study recommend universities to determine the interest of prospective students in continuing their education to a higher level through the influence of promotional strategies and social media to attract new prospective students.